Anggun Collection / Razman Ramli ... [et al.] - Ramli, Razman; Iska, Jainal; Baharudin, Nurul Haryana; Satimin, Hamizah; Zaiwai, Noor Zaihan; Ahmad, Shazwin Iryani (Faculty of Art and Design, 2004)
Anggun Collection is a partnership business that mainly sells and rents wedding costumes. The wedding clothes we made are mostly modern and contemporary design as well as the traditional ones to suit the Klang Valley urban taste and lifestyle. As wedding ceremony is a lifetime experience, we can make it a wonderful dream come true.